IMPROVING THE PRACTICE OF FEMINIZING SURGERY IN THE DEVELOPMENT OF GENITAL ORGANS - Shopulatov E.X. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Despite the progress made in the treatment of disorders of sex development, many aspects of birth defects remain controversial and controversial. In particular, the methods of reconstructive plastic surgery that feminize them have not beyen fully resolved. The following article presents the clinical manifestations of several types of defects in the formation of the genital organs in girls.